The institution of tax remitter by the Tax Ordinance Act - Kalinowski, Marek (Studia Iuridica Toruniensia, 2021)
The institution of tax remitter is used in a relatively broad manner in Polish tax system. This justifies the need to deepen the analysis of this legal institution. The subject of this article is the analysis of the legal status of the tax remitter regulated by the Tax Ordinance. This issue was preceded by the presentation of views of tax law science on this legal institution. The analysis leads to the conclusion that the tax remitter is the subject of a separate tax relationship connecting him with the state or other public body than the relationship connecting the taxpayer with the latter entities. He performs his own obligation, but by paying the tax due from the taxpayer. Thus, it can be concluded that to some extent the tax remitter enters into some part of the taxpayer’s obligations, although the bundle of these obligations is partly different from the bundle of obligations imposed on the taxpayer.